Studies on the substrate-dependent photocatalytic properties of Cu2O heterojunctions. Issue 9 (26th January 2021) - Khasanah, Riza Ariyani Nur; Lin, Hui-Ching; Ho, Hsiang-Yun; Peng, Yen-Ping; Lim, Tsong-Shin; Hsiao, Hsi-Lien; Wang, Chang-Ren; Chuang, Min-Chieh; Chien, Forest Shih-Sen
Abstract : Cu2 O/TNA/Ti photoanode showed spectral response outperformed Cu2 O/Ti and Cu2 O/FTO photocathodes. Cu2 O/TNA/Ti showed better spectral response than that of TNA/Ti, ascribed to UV-visible light absorption of Cu2 O, not to charge separation enhancement. Abstract : Cu2 O is a promising material for photocatalysis because of its absorption ability in the ultraviolet (UV)-visible light range. Cu2 O deposited on conductive Ti and fluorine-doped tin oxide (FTO) substrates behaves as a photocathode. Cu2 O deposited on an n-type semiconductor such as TiO2 nanotube arrays (TNA)/Ti behaves as a photoanode and has demonstrated better photocatalytic activity than that of TNA/Ti. The substrate-dependent photocatalytic properties of Cu2 O heterojunctions are not well studied. In this work, the photocatalytic properties of a Cu2 O/TNA/Ti junction as a photoanode and of Cu2 O/Ti and Cu2 O/FTO junctions as photocathodes without bias were systematically studied to understand their performance. The Cu2 O/TNA/Ti photoanode exhibited higher photocurrent spectral responses than those of Cu2 O/Ti and Cu2 O/FTO photocathodes. The photoanodic/photocathodic properties of those junctions were depicted in their energy band diagrams. Time-resolved photoluminescence indicated that Cu2 O/TNA/Ti, Cu2 O/Ti, and Cu2 O/FTO junctions did not enhance the separation of photogenerated charges. The improved photocatalytic properties of Cu2 O/TNA/Ti compared with TNA/Ti were mainly attributed to the UV-visible light absorption of Cu2 O.